PERCEPTION OF KKN STUDENTS TOWARD HYPERACTIVE BEHAVIOR OF JABAL NUR STUDENTS IN SEMPAJAYA VILLAGE DURING TEACHING AND LEARNING ACTIVITIES - Sapri; Rahmad Fauzi Hasibuan; Hadis Agsa Shifa; Dinda Sakinah Pohan; Rika Rahmadani; Agmi Rayhani (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
The teaching and learning process is not only influenced by teaching methods, but also by environmental factors, including temperature conditions. An interesting phenomenon is occurring at Jabal Nur School in Sempajaya Village, where students often exhibit hyperactive behavior during teaching and learning activities due to the village's location at the foot of a mountain. Students participating in the Community Service Program (KKN) who are placed in that village have the opportunity to observe and assess this phenomenon, making their perceptions important to study. This research uses a descriptive qualitative approach. The research subjects are KKN students assigned to Sempajaya Village. Data was collected thru observation, interviews, and documentation. The research results indicate that KKN students perceive the students of Jabal Nur as being more active, having difficulty focusing, and being restless during the learning process in the classroom. This hyperactive behavior is considered the body's response to warm itself up. Students also found that hyperactivity impacted the classroom atmosphere, making it less conducive, although there was individual variation in response levels to cold temperatures. The perception of KKN students indicates a relationship between cold temperatures and students' hyperactive behavior. This phenomenon aligns with the theory that environmental factors can influence learning behavior. Therefore, teachers and school authorities need to consider learning strategies and environmental adjustments so that students can still learn optimally even in low-temperature conditions.